Artificial Intelligence in Architecture: Its Influence on Design Processes - Suwal, Neha; Shrestha, Pramisha; Panthi, Sampanna; Sitaula, Yana; Shrestha, Sweta (KEC Journal of Science and Engineering, 2026)
The paper investigates how Artificial Intelligence (AI) is affecting architecture, specifically through its effects on design, creativity and making architectural work more effective. It investigates how AI can be used in architectural design, for creating sketches, analysing the site and automating records. The paper discusses uses of AI in examples such as Zaha Hadid Architects and Foster + Partners, along with revealing problems related to data, ethics, and skills development. According to the study, AI should be taught in architectural programs, appropriate tools made and principles for ethical use put in place.